Coach evaluation and recognition - Thibert, H. (The Professional Skater PS Magazine, 2021)
With permission to reprint from the "USOPC Quality Coaching Framework 2020" (assembled by the Coaching Education Department of the United States Olympic and Paralympic Committee) the Coach Development column has been a series of articles excerpted from the framework. On an individual level, all coaches should have a process to formally evaluate the progress of both their athletes and their own coaching. It may be that other sport struggle with this piece, PSA has a long history of doing a particularly good job with evaluation (PSA Ratings System) and recognition with the PSA Edi Awards annually.